1986
DOI: 10.1111/j.1744-6570.1986.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Computerized Interpretation System for Personnel Tests

Abstract: A computerized system was developed for generating narrative interpretations of scores from a battery of personnel screening tests. The report structure and interpretive statement library were designed to capture the test expertise and interpretive strategies of a panel of testing experts. This was accomplished by enumerating the questions that the experts believed the battery could answer, developing answers to these questions, and devising rules for selecting the appropriate answers based on test‐battery sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…In addition, the first paper published in MIS Quarterly was published by DeSanctis (1986) who investigated how organizations were using technology to support human resources. It is interesting that the first paper published in a major HR and psychology journal was also published in 1986 and that it is focused on using computers to interpret the results from selection tests (Vale, Keller, & Bentz, 1986).…”
Section: Hris Milestonesmentioning
confidence: 99%
“…In addition, the first paper published in MIS Quarterly was published by DeSanctis (1986) who investigated how organizations were using technology to support human resources. It is interesting that the first paper published in a major HR and psychology journal was also published in 1986 and that it is focused on using computers to interpret the results from selection tests (Vale, Keller, & Bentz, 1986).…”
Section: Hris Milestonesmentioning
confidence: 99%
“…The test score estimates of the expert raters generally underestimated the obtained test scores. Vale and Keller (1984) concluded that the narratives of the automated interpretive system was comparable to the narratives of the manually derived interpretive system.…”
Section: Exploring the Accuracy Of Cbti Outputmentioning
confidence: 95%
“…This meant that the expert interpreters were able to rate the output based on their understanding of the interpretive model. Vale and Keller (1984) conducted a validation study of an interpretive system that included measures in the following areas: mental ability, personality, values and interests. The four measures had been applied manually to screen individuals for an executive managerial training program.…”
Section: Exploring the Accuracy Of Cbti Outputmentioning
confidence: 99%
“…Although the general weaknesses in analysing test results cannot be denied, it has to be acknowledged that some programs go beyond scoring, assigning norms and graphically illustrating results: the interpretation of data (Booth 1986 Vale et al 1986) should also be considered in relation to the discussion about statistical vs. clinical judgement (Dawes 1971;Hanis 1987;Jager 1986,236ff .). Vale and Keller (1987) differentiate three types of approaches for interpreting data with computer assistance: -The term descriptive (program) systems is used to refer to systems that assign interpretative statements to test results.…”
Section: Scoring and Interpreting Questionnairesmentioning
confidence: 99%